Dependence of composition of asphaltene-resin-wax deposits on the water cut value; Petroleum Chemistry; Vol. 56, iss. 8 - Kirbizhekova E. V.; Prozorova I. V.; Nebogina N. A. Nadezhda Aleksandrovna; Grinko A. A. Andrey Alekseevich; Yudina N. V. Nataljya Vasiljevna (2016, 2016)
Title screen